Individual and Collective Self-Efficacy for Teaching Writing in a Multidisciplinary Sample of Canadian Faculty - Mitchell, Kim M. (Discourse and Writing/Rédactologie, 2024)
Background: Teacher self-efficacy can be defined as the confidence teachers hold about their individual and collective capacity to influence student learning. While many faculty assign and assess student writing as part of their course activities, they often perceive the act of writing as separate from rather than complementary to their teaching of subject matter content. This paper will report on the combined findings of two large survey studies of 385 faculty at Canadian universities, polytechnics and colleges. The purpose of the study was to assess faculty individual and collective self-efficacy for teaching writing.Methods: Data was collected from faculty via an electronic survey distributed by email or social media (Twitter). Faculty responded to the Individual and Collective Self-Efficacy for Teaching Writing Scales. They also responded to open-ended questions asking them to relate how they felt about their abilities to guide student writing.Results: Participants’ average age was 49.9 years with 14.5 years of teaching experience. Participants reported their individual self-efficacy for teaching writing at 77.2% while feeling that their departments as a whole were only 60% confident at teaching writing. Higher individual self-efficacy for teaching writing were found in faculty who were in combined research and teaching positions, PhD prepared, with prior formal education in teaching writing, and with 20 or more years of teaching experience. No statistically significant findings were observed with the Collective Self-Efficacy scale. From the qualitative survey data three themes were identified: 1) Blaming and lamenting; 2) Is teaching writing our responsibility? 3) Hopeful efforts and recognitions.Conclusion: Overall, the data is rife with narratives of blaming students and institutions for student inability to write and faculty questioning their role as writing instructor. These narratives drown out the narratives of faculty who have a passion for teaching writing. Future research should focus on the development of formalized workshops to support faculty teaching writing and changing their attitudes toward the developmental and disciplinary shared responsibility of writing instruction in higher education.